Cody Berndsen: capstone - Berndsen, Cody, artist (Colorado State University. Libraries, 2014)
The artist's statement: My experience at CSU has resulted in learning a wide spread of artistic methods and techniques. I have also learned how to expand my creative thinking and apply it to my work. It was through graphic design that I was really able to convey my artistic thoughts into a piece of work. What is so great about Graphic design is that it is a large mix of many types of art. For one single tabloid assignment I could implement drawing, painting and typography to create a good-looking composition. I love that I don't really have to choose one single method. I also enjoy being able to cross-pollinate the mediums digitally. I can draw something on paper and scan it in to an adobe program to give the drawing some really bold colors and thick outlines to create an even better illustration. It's these kinds of endeavors that have really allowed me to boost my artistic abilities. Studying at CSU, I also learned how to discuss my work and use design vocabulary to effectively create a good image. There is a specific process behind every piece of work and being placed in an environment where I can constantly get feedback from teachers and other designers is an important factor in each process. I hope I can take each skill I've acquired and utilize each of them for the real world when I graduate.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.